The effect of intravitreal anti-VEGF agents on peripheral wound healing in a rabbit model - Christoforidis J (Dove Medical Press, 2012)
John Christoforidis1, Robert Ricketts1, Cedric Pratt1, Jordan Pierce1, Scott Bean1, Michael Wells1, Xiaoli Zhang2, Krista La Perle31College of Medicine, 2Center for Biostatistics, 3College of Veterinary Medicine, The Ohio State University, Columbus, OH, USAPurpose: To investigate the effect of intravitreal pegaptanib, bevacizumab, and ranibizumab on blood-vessel formation during cutaneous wound healing in a rabbit model and to compare this effect to placebo controls.Methods: Forty New Zealand albino rabbits underwent full thickness cutaneous wounds using 6-mm dermatologic punch biopsies. The rabbits were assigned to four groups of ten, each receiving intravitreal injections of pegaptanib, bevacizumab, ranibizumab, or no injection (untreated controls). Five rabbits from each group underwent wound harvesting on day 7 and five from each group on day 14. The skin samples were stained with hematoxylin and eosin (HE), Masson's trichrome (MT), and CD34 for vascular endothelial cells. Semiquantitative evaluation of HE- and MT-stained slides was performed by one pathologist. Quantitative assessment of mean neovascularization (MNV) scores was obtained from five contiguous biopsy margin 400× fields of CD34-stained sections by four independent observers.Results: Week 1 MNV scores in CD-34 stained sections were: untreated controls: 11.51 ± 4.36; bevacizumab: 7.41 ± 2.82 (P = 0.013); ranibizumab: 8.71 ± 4.08 (P = 0.071); and pegaptanib: 10.15 ± 5.59 (P = 0.378). Week 2 MNV data were: untreated controls: 6.14 ± 2.25; bevacizumab: 7.25 ± 2.75 (P = 0.471); ranibizumab: 4.53 ± 3.12 (P = 0.297); and, pegaptanib: 6.35 ± 3.09 (P = 0.892). Interobserver variability using intraclass correlation coefficient was 0.961.Conclusions: At week 1, all three anti-VEGF agents had suppressed MNV scores compared to controls. Although not statistically significant, there was an inhibitory trend, particularly with bevacizumab and ranibizumab. These effects were diminished at 2 weeks, reflecting a transition between the proliferative and remodeling phases of wound healing.Keywords: anti-VEGF, wound healing, intraocular, pegaptanib, bevacizumab, ranibizumab